Probiotics and functional nutrition products - Yu. О. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To characterize treatment-andprophylactic effect of probiotics, concept of «functional nutrition» and its value in the pattern of human nutrition.Main contents. Medical and prophylactic effects of probiotics include increase of resistance to infectious diseases of intestine and respiratory tract, prevention and decrease of diarrhea duration, improvement of lactose tolerance, treatment of constipation, decrease of atopic reactions tendency, etc. Used strains can have direct effect on permeability of intestinal barrier and immunodefence components: increase of immunoglobulin A production, modify activity of phagocytes and natural killers, cytokine production and signaling endocellular molecules. Some medical strains reduce risk of atopic reactions. Strains, proven as effective agents for prophylaxis of widespread diseases, are added to functional nutrients. Fermented-milk product enriched by L. casei DN-114001 Imunitass, in controlled clinical studies demonstrated protective effect for the most of common infectious diseases. The probiotic fermented-milk product enriched by B. animalis DN-173 010 (ActiRegularis), has convincing evidential base for positive effect on frequency of bowel movements.Conclusion. Application of probiotics has major prospects as «physiologic» and safe method of stimulation of protective body resources. One of the ways to provide wider «operation» of preventive effect – is addition to fermented-milk products for daily intake.